Phenotypic plasticity enables considerable acclimation to heat and drought in a cold-adapted boreal forest tree species - Ravn, Jacob; D’Orangeville, Loïc; Lavigne, Michael B.; Taylor, Anthony R. (Frontiers in Forests and Global Change, 2022)
Increasing frequencies of severe heat waves and drought are expected to influence the composition and functioning of ecosystems globally. Our ability to predict and mitigate these impacts depends on our understanding of species- and age-specific responses to these stressors. To assess the adaptive capacity of balsam fir to climate change, a cold-adapted boreal tree species, we conducted a climate-controlled greenhouse experiment with four provenances originating from across the species biogeographic range, 12 temperature treatments ensuring a minimum of +11°C warming, and five drought treatment intensities. We found considerable acclimation to temperature and drought treatments across all provenances, with steady gains in biomass under temperatures well-beyond the “worst-case” (RCP 8.5) climate forcing scenario within the species natural range. Acclimation was supported by high phenotypic plasticity in root:shoot ratio and photosynthesis, which were greatly increased with warming, but were not affected by drought. Our results suggest that regardless of the observed provenance variation, drought and heat are not limiting factors of the current-year balsam fir seedling growth, instead, these factors may be more impactful on later stages of regeneration or previously stressed individuals, thus highlighting the necessity of incorporating the factors of ontogeny and provenance origin in future research regarding plant and climate interactions.